Industrial Applications of Terahertz Sensing: State of Play - Mira Naftaly; Nico Vieweg; Anselm Deninger (Sensors, 2019)
This paper is a survey of existing and upcoming industrial applications of terahertz technologies, comprising sections on polymers, paint and coatings, pharmaceuticals, electronics, petrochemicals, gas sensing, and paper and wood industries. Finally, an estimate of the market size and growth rates is given, as obtained from a comparison of market reports.